Dynamics of dewetting and bubble attachment to rough hydrophobic surfaces – Measurements and modelling. (January 2016) - Zawala, Jan; Kosior, Dominik
Highlights: Time of bubble attachment to hydrophobic solid depends on solid surface roughness. It is much shorter for rough hydrophobic surface comparing to smooth one. Results obtained suggest air-induced rupture of the liquid (wetting) film formed. Different amount of interfacial air facilitates the liquid film rupture. Different amount of means variations in the solid hydrodynamic boundary conditions. Abstract: The influence of solid surface roughness (hydrophobic Teflon®) on the timescale of the ascending air bubble ( Rb = 0.74 mm) attachment and the kinetics of the spreading of the three-phase contact (TPC – gas/liquid/solid) line was studied. The moment of the rising bubble collision with a horizontal Teflon® plate immersed in ultrapure water was monitored using fast video recordings (4000 fps). It was shown that, depending on the solid surface roughness, the time of the TPC formation was significantly different. Similarly to our previous studies, it was shorter for higher roughnesses. Using high-frequency video acquisition, an additional factor, kinetics of the spreading of the TPC line associated with various bubble shape changes during TPC formation, could be determined. The registered attachment kinetics and bubble shape variations were very reproducible for smooth and very rough Teflon® surfaces, whereas for Teflon® of intermediate roughness, up to five different attachment scenarios were observed, with a relatively large standard deviation of time of TPC formation. Numerical calculations used for simulation of the bubble collisions with a horizontal solid wall with precisely controlled hydrodynamic boundary conditions revealed that the experimentally observed timescales of the bubble attachment and spectacular bubble shape variations can be accurately (qualitatively) reproduced for each roughness of the Teflon® plate studied. Good agreement between experimental and numerical data is, in our opinion, rather strong evidence for air-induced rupture of the liquid film formed between the colliding bubble and the hydrophobic solid plate. This supports the hypothesis that depending on the solid surface roughness, different amounts of air entrapped in solid surface irregularities could drastically change the solid surface hydrodynamic boundary conditions and, consequently, the kinetics of spreading and formation of the TPC.